Processing map to control the erosion of Y2O3 in fluorine based etching plasmas. Issue 5 (15th January 2022) - Kindelmann, Moritz; Weber, Moritz L(ukas); Stamminger, Mark; Buschhaus, Rahel; Breuer, Uwe; Bram, Martin; Guillon, Olivier
Abstract: Due to the increasing number of applications for ceramic components in reactive etching processes, the interest in the specific erosion behavior of highly etch‐resistant materials like yttrium oxide (Y2 O3 ) has increased in the past years. Despite the large number of investigations already existing in this field, a more general understanding of the erosion mechanisms still lacks due to the limited comparability of these investigations. The huge difference in the kind of etching setups, processing parameters (bias voltage and plasma gas composition), and sample microstructures prevented consistent conclusions so far. To achieve a more general understanding, this study investigates the erosion behavior Y2 O3 under a broad spectrum of plasma etching parameters. Therefore, the bias voltage is increased from 50 to 300 V and the plasma gas composition is gradually changed from Ar‐rich to CF4 ‐rich compositions. This systematic approach allows to directly correlate the morphology changes caused by plasma erosion with the related plasma etching parameters and enables to better understand their influence on the depth of physical and chemical interactions, surface damage, and etching rate. We discovered three distinct erosion regimes, which exhibit specific erosion characteristics. Using these observations, a schematic processing map for Y2 O3 was developed, which could help to estimate the severity of the erosion attack dependent on the processing parameters. Abstract :